2011
DOI: 10.1007/s10529-011-0636-2
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of biologically-active human interferon-β by Bacillus subtilis

Abstract: Human interferon-β (hIFN-β) was used as a heterologous model protein to investigate the effects of the Bacillus subtilis AmyE propeptide and co-expression of PrsA in enhancing the secretion of heterologous proteins in B. subtilis. Secretion and activity of hIFN-β with AmyE propeptide increased by more than four-fold compared to that without AmyE propeptide. Moreover, under conditions of co-expressed PrsA, the secretion production and activity of hIFN-β with AmyE propeptide increased by more than 1.5-fold. AmyE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…Gram-positive organisms, exported proteins commonly contain a propeptide sequence, which follows the export signal sequence and increases export efficiency (23). The AmyE propeptide from the ␣-amylase of B. subtilis is 11 amino acids long (ETANKSNELTA) and contains no proline residues.…”
Section: The Binding Of Prsa To Presequence Involves Residues From Thmentioning
confidence: 99%
See 2 more Smart Citations
“…Gram-positive organisms, exported proteins commonly contain a propeptide sequence, which follows the export signal sequence and increases export efficiency (23). The AmyE propeptide from the ␣-amylase of B. subtilis is 11 amino acids long (ETANKSNELTA) and contains no proline residues.…”
Section: The Binding Of Prsa To Presequence Involves Residues From Thmentioning
confidence: 99%
“…The AmyE propeptide from the ␣-amylase of B. subtilis is 11 amino acids long (ETANKSNELTA) and contains no proline residues. When attached to other proteins, it improves their export (23,72). If PrsA is overexpressed in addition to the AmyE attachment, the protein export is further increased (23), suggesting functional interplay and possibly a direct interaction of PrsA and the AmyE propetide.…”
Section: The Binding Of Prsa To Presequence Involves Residues From Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The secretion production and activity of hIFN-β with propeptide increased by more than 4-fold (Fig. 4, Kakeshita et al, 2011b). The amount of secreted hIFNwww.intechopen.com β with propeptide was 3.7mg /L.…”
Section: Propeptidementioning
confidence: 92%
“…Arrowheads indicate the positions of the Pro-hIFN-β and hIFN-β. (adapted from Kakeshita et al, 2011b) In L. lactis, directed mutagenesis experiments demonstrated that the positive effect of LEISSTCDA on protein secretion was due to the insertion of negatively charged residues in the N-terminus of the mature moiety (Le Loir et al, 2001). In hIFN-α2b with AmyE propeptide, the first 10 amino acid residues of this mature protein have a net charge of -1.…”
Section: Propeptidementioning
confidence: 99%